STRATEGI SUPEVISOR DALAM PEMBINAAN PADA PERUBAHAN KURIKULUM 2013 KE KURIKULUM MERDEKA - Drs. H. Sarkati M.Ag (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
Curriculum changes will indeed continue to occur so that adjustments are needed so that education continues to run well, even the current curriculum change is the 2013 curriculum to an independent curriculum so that it requires a strategy. Strategy is a design pattern or series of activities chosen to make it easier to achieve goals. To make adjustments, one of them is to hold coaching. Therefore, what kind of strategy can be used by a supervisor or supervisor in coaching on curriculum changes. The aim is to provide an overview of how the curriculum will be used, namely the independent curriculum, to provide insight to education providers, especially educators about independent learning, and to help educational units adapt to the times. The method used in this research is literature study or literature study using a qualitative approach. The results of this study are that one of the coaching that can be done is by conducting training and mentoring which is led directly by the supervisor.